Reusable magnetic nanocatalyst for bio-fuel additives: the ultrasound-assisted synthesis of solketal dagger - Rajkumari, Kalyani; Changmai, Bishwajit; Meher, Ananta Kumar; Vanlalveni, Chhangte; Sudarsanam, Putla; Wheatley, Andrew E. H.; Rokhum, Samuel Lalthazuala (Sustainable Energy & Fuels, 2021)
Acetalization of glycerol into solketal, a potential fuel additive, is a promising approach to utilizing the large waste-stream of glycerol from the biodiesel industry. Herein, we report an efficient ultrasound-assisted room temperature synthesis of solketal by acetalization of glycerol with acetone using an easily recoverable sulfonic acid-functionalized, silica-coated Fe3O4 magnetic nanoparticle (Fe3O4@SiO2@SO3H MNP, FSS MNP) catalyst. The morphology, chemical composition and magnetic properties of the catalyst were elucidated. The acetalization of glycerol was carried out under ultrasonication at room temperature, resulting in 97% glycerol conversion after 15 minutes and 95% isolated yield of solketal with 100% selectivity for this acetal. The facile magnetic retrievability of the catalyst imparted operational simplicity to the solketal synthetic protocol, avoiding complicated catalyst separation and product purification processes. The FSS catalyst was magnetically recycled for up to five catalytic experiments, maintaining a glycerol conversion of 95% and without deterioration in its selectivity, composition, morphology or magnetic properties, thereby ameliorating the green aspects of the protocol.